Effect of Kelor Leaves (Moringa oleifera) in Liver Function of Streptozotocin induced Diabetic Sprague dawley Strain Male Rats - Nashih Abdillah; Devy Ariany; Muniroh . Muniroh (Faculty of Medicine, UIN (State Islamic University) Syarif Hidayatullah Jakarta, 2022)
Background: Diabetes mellitus (DM) is a metabolic disease characterized by hyperglycemia. Prolonged hyperglycemia can damage various organs of the body including the liver. Moringa oleifera leaves extract contain flavonoids which can decrease blood glucose levels and act as a hepatoprotector. To evaluate its hepatoprotective activity, liver function marker Serum glutamic oxaloacetic transaminase (SGOT) and serum glutamic pyruvate transminase (SGPT ) was used. In this study, we aimed to determine the effect of Moringa oleifera leaves extract on the liver function test of male Sprague dawley rats that have DM due to streptozotocin induction.Methods: This was experimental study conducted from February 2019 to July 2019 at Faculty of Medicine Laboratory, UIN Syarif Hidayatullah, Jakarta. This study conducted in 25 male Sprague dawley rats divided into 5 groups, those were negative controls group, positive controls group, and 3 treatment groups which given oral Moringa oleifera leaves extract at doses of 200 mg/kgBW, 400 mg/kgBW, and 600 mg/kgBW, respectively, for 14 days. Samples were collected on day 26th to measure SGOT and SGPT. Blood glucose levels were assayed on day 6th and 26th.Results: There was no significant decrease in SGOT (p=0.069) and SGPT (p=0.345) levels in the administration of Moringa oleifera leaves extract to male Sprague dawley rats with DM induced by streptozotocin at a dose of 200 mg/KgBW and 400 mg/KgBW.Conclusions: Moringa oleifera leaves extract did not significantly decrease SGOT and SGPT.